2022
DOI: 10.3389/fonc.2022.836934
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Medication Effects on Immune Checkpoint Inhibitor Efficacy and Toxicity

Abstract: There are multiple approved indications for immune checkpoint inhibitors (ICI) in patients with advanced solid tumors. Polypharmacy, defined as the use of ≥ 5 medications, is common among cancer patients. The impact of these non-oncologic medications on ICI efficacy or the development of side effects, specifically immune related adverse events (irAEs), is unclear. Recent clinical studies investigating the connection between concomitant medications and ICI efficacy have produced conflicting results. A systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…On the contrary, a retrospective study of 330 patients with metastatic melanoma did not find an association between NSAID use and improved outcomes [ 9 ]. Similarly, Sieber et al showed similar rates of clinical benefits regardless of aspirin use among patients receiving ICI therapy for solid tumors in a meta-analysis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a retrospective study of 330 patients with metastatic melanoma did not find an association between NSAID use and improved outcomes [ 9 ]. Similarly, Sieber et al showed similar rates of clinical benefits regardless of aspirin use among patients receiving ICI therapy for solid tumors in a meta-analysis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that altered gut microbiota negatively impacts patient survival outcomes, primarily through acquired resistance mechanisms (Routy et al 2018). In particular, medications that affect the immune homeostasis and gut microbiota, such as antibiotics (ATBs), corticosteroids (CSs), proton-pump inhibitors (PPIs), and opioids, have been shown to affect the e cacy of ICIs (Colard-Thomas et al 2023;Hussain et al 2021;Sieber et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that altered gut microbiota negatively impacts patient survival outcomes, primarily through acquired resistance mechanisms (Routy et al 2018). In particular, medications that affect the immune homeostasis and gut microbiota, such as antibiotics (ATBs), corticosteroids (CSs), proton-pump inhibitors (PPIs), and opioids, have been shown to affect the e cacy of ICIs (Colard-Thomas et al 2023;Hussain et al 2021;Sieber et al 2022). However, the impact of concurrent medications on the treatment outcomes of ICI-treated patients with cancer is not demonstrated well in population-based studies, as most previous studies are small-scale retrospective analyses of patients in clinical trials or single-center studies.…”
mentioning
confidence: 99%
“…Evidence suggests that altered gut microbiota negatively impacts patient survival outcomes, primarily through acquired resistance mechanisms (Routy et al 2018 ). In particular, medications that affect the immune homeostasis and gut microbiota, such as antibiotics (ATBs), corticosteroids (CSs), proton-pump inhibitors (PPIs), and opioids, have been shown to affect the efficacy of ICIs (Colard-Thomas et al 2023 ; Hussain et al 2021 ; Sieber et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%